Insights into nano-mechanical degradation behavior of Ag/Ti2AlC composite under different arc erosion stages - Wanjie Sun; Yuxin Shi; Chengzhe Wu; Xinpeng Wei; Yundeng Zhang; Gege Li; Liming Chen; Chengjian Ma; ZhengMing Sun; Peigen Zhang; Jianxiang Ding (Journal of Materials Research and Technology, 2023)
Serious arc erosion is the main reason for premature failure of the Ag-matrix composite electrical contact materials in actual service. Clarifying the structure and property degradation process is crucial for creating eco-friendly Ag/MAX electrical contacts and upgrading high-performance materials for low-voltage switch applications. In this study, the representative Ag/Ti2AlC electrical contacts were designed into three arc erosion stages (from 1 to 5610 cycles) by ex-situ arc discharging experiment, and the nanoindentation technique was then applied to in-depth analyze the evolution behavior of nano-mechanical properties by comparing nano hardness, modulus, creep, continuous stiffness, elastic/plastic deformation, and NanoBlitz 3D Mapping indentation results in different erosion stages. Finally, the inherent relationship among the structural dissociation of Ti2AlC, and compositional changes of Ag/Ti2AlC interface and nano-mechanical properties of composite was revealed, and the material degradation model and anti-arc erosion mechanism were proposed. This work further elucidates the intrinsic source of excellent arc erosion resistance and degradation process of Ag/Ti2AlC composite from the nano-mechanical perspective and lays a theoretical foundation for the future design and optimization of this material system.